Before the disaster: notes on Journalism, risk communication, prevention and citizen involvement - Beling Loose, Eloisa; Tourinho Girardi, Ilza Maria (Mediaciones Sociales, 2018)
This text, from a reflective perspective, articulates aspects related to the risks communication, the involvement of citizens and the place given to prevention by journalism. From a bibliographical research, it is verified that this interface is still restricted in Brazil and, from the literature discussion, the possible crosses between the culture of prevention and the journalistic coverage about risks, as well as their association with citizenship, are analyzed. Among the considerations, it points out that Journalism needs to revise its logic, focused on the present, to the concrete event, since we are living in a society oriented to the future and surrounded by risks - which requires a more preventive positioning.
Keywords: Journalism; Risks communication; Prevention.